Assessment of unintentional acute pesticide poisoning among smallholder vegetable farmers in Trinidad and Jamaica - Robinson, Dwight E.; Stuart, Alexander M.; Willis, Sheila; Salmon, Joey P.; Ramjattan, Jeet; Ganpat, Wayne; Williamson, Stephanie; Tyrell, Keith F.; Saravanakumar, Duraisamy (Frontiers in Public Health, 2024)
Poisoning caused by pesticides is widely recognized as a major public health problem among smallholder farmers and rural communities, including in the Caribbean. However, a lack of quality data impedes understanding of the problem and hampers the development of effective strategies for its management. To better understand the prevalence of unintentional acute pesticide poisoning (UAPP) in Trinidad and Tobago and Jamaica and the pesticides and practices involved, we conducted a cross-sectional survey of 197 and 330 vegetable farmers in Trinidad and Jamaica, respectively. The findings from this study revealed a high incidence of self-reported health effects from occupational pesticide exposure, with 48 and 16% of respondents, respectively, experiencing symptoms of UAPP within the previous 12 months. Furthermore, the substantial proportion of UAPP incidents were associated with a few highly hazardous pesticides (HHPs), particularly lambda-cyhalothrin, acetamiprid, and profenofos in Jamaica, and alpha-cypermethrin, paraquat and lambda-cyhalothrin in Trinidad. Given the well-documented adverse effects of these chemicals on human health, the results of this study should be of significant concern to health authorities in Jamaica and Trinidad. This clearly indicates an urgent need for improved regulation and safer alternatives to the use of HHPs, as well as the promotion of alternatives. We provide policy recommendations and identify alternatives to HHPs for tropical vegetable production.